Optimization and Lead Selection of Benzothiazole Amide Analogs Toward a Novel Antimycobacterial Agent - De Groote, Mary A.; Jarvis, Thale C.; Wong, Christina; Graham, James; Hoang, Teresa; Young, Casey L.; Ribble, Wendy; Day, Joshua; Li, Wei; Jackson, Mary; Gonzalez-Juarrero, Mercedes; Sun, Xicheng; et al. (Frontiers in Microbiology, 2018)
ABSTRACT Mycobacteria remain an important problem worldwide, especially drug resistant human pathogens. Novel therapeutics are urgently needed to tackle both drug-resistant tuberculosis (TB) and difficult-to-treat infections with nontuberculous mycobacteria (NTM). Benzothiazole adamantyl amide had previously emerged as a high throughput screening hit against M. tuberculosis (Mtb) and was subsequently found to be active against NTM as well. For lead optimization, we applied an iterative process of design, synthesis and screening of several hundred analogs to improve antibacterial potency as well as physicochemical and pharmacological properties to ultimately achieve efficacy. Replacement of the adamantyl group with cyclohexyl derivatives, including bicyclic moieties, resulted in advanced lead compounds that showed excellent potency and a mycobacteria-specific spectrum of activity. MIC values ranged from 0.03-0.12 µg/mL against M. abscessus (Mabs) and other rapid- growing NTM, 1-2 µg/mL against M. avium complex (MAC), and 0.12-0.5 µg/mL against Mtb. No pre-existing resistance was found in a collection of n=54 clinical isolates of rapid-growing NTM. Unlike many antibacterial agents commonly used to treat mycobacterial infections, benzothiazole amides demonstrated bactericidal effects against both Mtb and Mabs. Metabolic labeling provided evidence that the compounds affect the transfer of mycolic acids to their cell envelope acceptors in mycobacteria. Mapping of resistance mutations pointed to the trehalose monomycolate transporter (MmpL3) as the most likely target. In vivo efficacy and tolerability of a benzothiazole amide was demonstrated in a mouse model of chronic NTM lung infection with Mabs. Once daily dosing over 4 weeks by intrapulmonary microspray administration as 5% corn oil/saline emulsion achieved statistically significant CFU reductions compared to vehicle control and non-inferiority compared to azithromycin. The benzothiazole amides hold promise for development of a novel therapeutic agent with broad antimycobacterial activity, though further work is needed to develop drug formulations for direct intrapulmonary delivery via aerosol.